-11=m+12m

Simple and best practice solution for -11=m+12m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11=m+12m equation:


Simplifying
-11 = m + 12m

Combine like terms: m + 12m = 13m
-11 = 13m

Solving
-11 = 13m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-13m' to each side of the equation.
-11 + -13m = 13m + -13m

Combine like terms: 13m + -13m = 0
-11 + -13m = 0

Add '11' to each side of the equation.
-11 + 11 + -13m = 0 + 11

Combine like terms: -11 + 11 = 0
0 + -13m = 0 + 11
-13m = 0 + 11

Combine like terms: 0 + 11 = 11
-13m = 11

Divide each side by '-13'.
m = -0.8461538462

Simplifying
m = -0.8461538462

See similar equations:

| x^2-x-18=-2x+2 | | 5x+7=7x+27 | | 3/7=6/15 | | 6xsquare-37x=-6 | | 20m-14=10 | | 2(4+3m)=3 | | 2,5(x-2)-1,5x=1 | | 3(k+5)=-8 | | (X-4)=15 | | 6=(1/2)(5)(x) | | 2m+18=6m | | -5(10+2x)-2(x+4)=14 | | 9=8*-5+8 | | 2y/3-8=2y+3 | | -9(5-4x)-(3x+5)=49 | | 2(m+4)=6 | | -4(10-8y)=24 | | k/2-4=-7 | | 5(x+2)=4(x-6) | | 2x^(3/2)=250 | | 7x^8-7=0 | | 2(7-w)-4=0 | | -6=b/5-10 | | 2x^3/2=250 | | 2g-4=10h | | 3=-b-6 | | 9+x/4=5 | | 5x-4-2x+3=-7-3x+5+2x | | -160=2-9x | | -7x+3=-4 | | 6=1+5(y-2) | | 5x+8=4x-1 |

Equations solver categories